Intercondylar Notch Width in Dogs With and Without Cranial Cruciate Ligament Injuries - Aiken, S. W.; Kass, P. H.; Toombs, J. P. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
This prospective study evaluated the intercondylar notch width in dogs with naturally occurring cranial cruciate ligament (CCL) injuries. The intercondylar notch width was measured in 45 stifles with CCL injuries and 98 normal stifle joints to determine if stifles with CCL injuries have outlet stenosis of the intercondylar notch. A notch width index was calculated in order to compensate for the variety of dog sizes. Stifles with CCL injuries had significantly smaller notch width indices as compared to normal stifles. We concluded that intercondylar notchplasty should be performed if an intra-articular repair of the CCL deficient stifle is planned in order to minimize impingement of the stenotic intercondylar notch on the intra-articular graft.An intercondylar notch width index was determined in 45 stifles with cranial cruciate ligament (CCL) injuries and 98 normal stifle joints. Stifles with CCL injuries were found to have significantly smaller intercondylar notch width indices as compared to normal stifles.
Keywords: Intercondylar notch; cranial cruciate ligament; intercondylar notchplasty; canine